Short stature and pubertal delay in Duchenne muscular dystrophy. Issue 1 (3rd July 2015) - Wood, Claire L; Straub, Volker; Guglieri, Michela; Bushby, Kate; Cheetham, Tim
Abstract : Children with Duchenne muscular dystrophy (DMD) are shorter than their healthy peers. The introduction of corticosteroid (CS) has beneficial effects on muscle function but slows growth further and is associated with pubertal delay. In contrast to CS usage in most children and adolescents, weaning glucocorticoid is not a key objective of management in DMD. As the outlook for these young people improves, one of the main challenges is to reduce or offset the detrimental effects of CS on growth and development. This is a review of the aetiology and prevalence of short stature and delayed puberty in DMD, a summary of the treatments available and suggestions for areas of further research.